Benefits and Challenges of a Physical Device Farm for Automated Software Testing: A Case Study of the STELA Tool Implementation - Chaves, Lennon; Oliveira, Flavia; Tiago, Leonardo; Castro, Renata (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2024)
Software testing ensures seamless user experience that is achievable through manual or automated testing. Automated testing offers benefits, such as time reduction and parallel task execution. Physical device farms are used to conduct automated tests across different Android versions. The Software Test Execution Lab for Automation (STELA), designed as a Physical Device Farm, was recently implemented at a software institute by an automation team. This tool, housed in a lab with a capacity of 400 mobile devices, aided the testing team in executing automated tests. Interviews with 22 testing team members highlighted time optimization and a simplified interface as the primary benefits of STELA. Since its implementation, approximately 979 tests have been conducted, saving approximately 1915 minutes. This study examines the pros and cons of using a Physical Device Farm for software testing.